Efektifitas Proses Koagulasi-Flokulasi Dalam Menyisihkan Parameter TSS Dan TDS Pada Limbah Cair Laboratorium Kimia Dasar - Audina, Nurul; Elystia, Shinta; HS, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Coagulation and flocculation process is used because of it’s ability to remove colloids and suspended particles that contained in laboratory wastewater. The wastewater of Fundamental Chemical Laboratory contained very high concentrations of TSS and TDS, therefore coagulation and flocculation process is needed. This research was conducted to determine the optimum coagulant dose of PAC (Polyaluminium Chloride) in remove TSS and TDS. The determine of optimum coagulant is done by varies doses of PAC within 400, 500, 600, and 700 mg/L. Jar test method resulting the optimum condition of coagulant PAC is in 600 mg/L. Based on the result, the final concentration of TSS and TDS have met the Type II waste water quality standards, but TDS concentrations are still above the Type I waste water quality standards.Keywords: Laboratory Wastewater, Coagulation, Flocculation, Poly AluminiumChloride (PAC), TSS, TDS.